Logistic Stewardship: Supporting Antimicrobial Stewardship Programs Based on Antibiotics Goods Flow - Bianca Leistner; Dominic Rauschning; Ralf Matthias Hagen; Franziska Srečec; Nico Tom Mutters; Ruth Weppler; Christina Mutschnik; Manuel Döhla (Antibiotics)
Background/Objectives: Antimicrobial resistance is a global threat to safe health care, and a reduction in antibiotic consumption seems to be an appropriate preventive measure. In Germany, the reporting of hospital antibiotics consumption to an independent institution is only voluntary. Although a high level of willingness to improve can be assumed in the case of participation, the median consumptions of reporting hospitals change only slightly. This study examines the question of whether the logistical consumption figures adequately reflect real consumption, and if not, how to optimize the use of logistical data for clinical decisions. Methods: Four selected wards were analyzed during six months. A retrospective analysis of patient case files was performed to receive “prescribed daily doses” (PDDs). These were compared to “defined daily doses” (DDDs) from logistical data. Additional inventories were performed to calculated stored antibiotics. Antibiotics goods flows were presented via waterfall diagrams to identify logistic patterns that could explain PDD/DDD quotients. Antimicrobial stewardship (AMS) quality indicators were analyzed to give advice for optimized clinical AMS measures. Results: The total PDD/DDD quotient was 0.69. Four logistical patterns were identified. Optimized prophylaxis, AMS consultations and reevaluation of therapy seem to be the most useful measures to reduce PDDs. Conclusions: If AMS programs rely solely on DDDs, measures cannot be optimal. A complete consideration of antibiotic goods flows supports clinical decisions, but is very costly in terms of data collection. The consideration of logistical data can help to identify areas of focus for AMS programs. Therefore, specialists of antibiotics logistics should complement clinical AMS teams.